2016
DOI: 10.3390/jintelligence4010005
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Worst Performance Rule as a Function of Task Complexity and Psychometric g: On the Crucial Role of g Saturation

Abstract: Within the mental speed approach to intelligence, the worst performance rule (WPR) states that the slower trials of a reaction time (RT) task reveal more about intelligence than do faster trials. There is some evidence that the validity of the WPR may depend on high g saturation of both the RT task and the intelligence test applied. To directly assess the concomitant influence of task complexity, as an indicator of task-related g load, and g saturation of the psychometric measure of intelligence on the WPR, da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 49 publications
3
24
1
Order By: Relevance
“…The worst performance rule has been conceptually replicated in many studies with different reaction time tasks, different samples and different age groups, e.g. in school children (Fernandez, Fagot, Dirk, & de Ribaupierre, 2014), undergraduate students (e.g., Diasco & Brody, 1992;Fernandez et al, RUNNING HEAD: A META-ANALYSIS OF THE WPR 7 2014; Kranzler, 1992;Leite, 2009;Schmiedek et al, 2007;Schmitz, Rotter, & Wilhelm, 2018;Unsworth et al, 2010), and age-heterogeneous community samples (e.g., Fernandez et al, 2014;Frischkorn, Schubert, Neubauer, & Hagemann, 2016;Rammsayer & Troche, 2016;Schmitz & Wilhelm, 2016). In addition, it has been suggested that the size of the worst performance effect, i.e.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…The worst performance rule has been conceptually replicated in many studies with different reaction time tasks, different samples and different age groups, e.g. in school children (Fernandez, Fagot, Dirk, & de Ribaupierre, 2014), undergraduate students (e.g., Diasco & Brody, 1992;Fernandez et al, RUNNING HEAD: A META-ANALYSIS OF THE WPR 7 2014; Kranzler, 1992;Leite, 2009;Schmiedek et al, 2007;Schmitz, Rotter, & Wilhelm, 2018;Unsworth et al, 2010), and age-heterogeneous community samples (e.g., Fernandez et al, 2014;Frischkorn, Schubert, Neubauer, & Hagemann, 2016;Rammsayer & Troche, 2016;Schmitz & Wilhelm, 2016). In addition, it has been suggested that the size of the worst performance effect, i.e.…”
mentioning
confidence: 89%
“…However, except for these two publications, none of the studies on the worst performance rule formally tested the worst performance rule as regression. Only one study statistically tested the difference of correlations between slowest and fastest reaction times (Rammsayer & Troche, 2016), and only a few studies calculated regressions of cognitive ability test performance on multiple RT quantiles to test if slowest reaction times predicted any variance in cognitive ability test performance beyond fastest and/or median reaction times (Fernandez et al, 2014;Salthouse, 1993;1998). The vast majority of studies on the worst performance rule instead only reported the course of correlations between reaction times and cognitive ability test performance across quantiles of the RT distribution and employed no formal test of the worst performance rule.…”
Section: ) the Lack Of Statistical Tests Of The Worst Performance Rulementioning
confidence: 99%
See 2 more Smart Citations
“…A second group of studies has focused more on the role of attentional or executive lapses in explaining RT‐ability effects and has shown that higher and lower ability participants differ not only in their median RTs but also in their proportion of long‐latency responses. This finding gives rise to the so‐called worst performance rule (Larson & Alderton, ), whereby RT‐ability correlations are often strongest for the slowest RTs (Frischkorn et al, ; McVay & Kane, ; Rammsayer & Troche, ; Schmiedek, Oberauer, Wilhelm, Süß, & Wittmann, ; Unsworth, Redick, Lakey, & Young, ). Finally, it should be noted that the speed of processing and executive control theories are not necessarily mutually exclusive and can both be represented via diffusion models, which construe RT as the outcome of a still lower‐order process of evidence accumulation (McVay & Kane, ; Ratcliff, Schmiedek, & McKoon, ; van Ravenzwaaij, Brown, & Wagenmakers, ; Schmiedek et al, ).…”
Section: Introductionmentioning
confidence: 99%